Teaching Chinese Language in Singapore Efforts and Possibilities (Springer Singapore, 2018)
This book presents the experiences of Chinese Language researchers in Singapore to Chinese Language researchers and teachers in other countries and regions, such as the USA, the UK and Asia, that are home to a large number of learners, young and old. As such, the innovative ideas it provides can be applied in practising teachers' classrooms to promote more effective and efficient student learning. Beyond pedagogical innovations, the book also includes papers on the assessment of Chinese Language learning and teacher literacy - two areas that have been largely neglected by the Chinese Language research and teaching communities, not only here in Singapore, but also around the world. This book, the sequel to "Teaching Chinese Language in Singapore: Retrospect and Challenges" (Springer, 2016), is future-oriented, highlighting ideas that merit further attention from researchers and practitioners alike.